2012
DOI: 10.1051/kmae/2012006
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Turkish narrow clawed crayfish (Astacus leptodactylus) populations carryAphanomyces astaci

Abstract: Crayfish stocks collapsed in Turkey in mid 1980's due to crayfish plague epidemics, with up to 25% survival in some cases. The collapsed stocks have then recovered slowly and commercial crayfish fishery was reinitiated gradually within a decade. We examined the prevalence of Aphanomyces astaci DNA in the narrow clawed crayfish (Astacus leptodactylus) collected from two Turkish lakes, Lake İznik and Hirfanlı Dam (N = 40 from both sites). The qPCR results, verified by conventional PCR and sequencing, indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 17 publications
(28 reference statements)
5
64
0
Order By: Relevance
“…Chitinase production has been claimed to be adaptation to parasitic life style and one of the virulence factors (Unestam, 1966;Hochwimmer et al, 2009). The reports of A. astaci adaptation to the European crayfish hosts (Jussila et al, 2011;Viljamaa-Dirks et al, 2011;Kokko et al, 2012;Svoboda et al, 2012;Kušar et al, 2013) are most probably all concerning As-genotype adaptation. The 150 year history in Europe, with high selection pressure, has caused a rather rapid co-evolution of both the host and the pathogen.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Chitinase production has been claimed to be adaptation to parasitic life style and one of the virulence factors (Unestam, 1966;Hochwimmer et al, 2009). The reports of A. astaci adaptation to the European crayfish hosts (Jussila et al, 2011;Viljamaa-Dirks et al, 2011;Kokko et al, 2012;Svoboda et al, 2012;Kušar et al, 2013) are most probably all concerning As-genotype adaptation. The 150 year history in Europe, with high selection pressure, has caused a rather rapid co-evolution of both the host and the pathogen.…”
Section: Figurementioning
confidence: 99%
“…In general, this disease has a bad reputation, but some A. astaci strains seem to show signs of avirulence (Jussila et al, 2011a;Makkonen, 2013). Certain strains of this parasite have likely adapted to their fairly recent European hosts, as the As-genotype is currently causing highly variable mortalities among native European crayfish both in laboratory experiments and among wild populations (Jussila et al, 2011Kokko et al, 2012;Svoboda et al, 2012;Caprioli et al, 2013;Kušar et al, 2013). So far, however, the evidence of virulence differences and potential evolution among PsI-genotype, or other more recently introduced A. astaci genotypes, has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the epidemics, the native European noble crayfish Astacus astacus is facing a high risk of extinction in the wild (Red List Category & Criteria: Vulnerable A2; IUCN Red List of threatened species) and therefore A. astaci is being listed among the 100 worldwide worst invasive species (Lowe et al 2004). The remaining European native crayfish populations, including noble crayfish, differ in their experience of crayfish plague infections, varying from acute disease epidemics to pristine populations without a known history of outbreaks (Jussila et al 2011b, Kokko et al 2012, Makkonen et al 2012b. Understanding of the dynamics of crayfish plague epidemiology is still ambiguous (Fürst 1995, Edgerton et al 2004 (Jussila et al 2011b, Viljamaa-Dirks et al 2011.…”
mentioning
confidence: 99%
“…This indicates that individual-and population-specific differences in disease resistance potentially play a role in the crayfish plague dynamics (Makkonen et al 2012b) and have prolonged the existence of the disease in certain waters. Furthermore, there are recent reports on population recoveries after crayfish plague epidemics among the Turkish narrow clawed crayfish populations (Harlioğlu 2008, Kokko et al 2012, Svoboda et al 2012. These crayfish carry the infection and are commercially exploited despite the lack of a long co-evolutionary history with A. astaci.…”
mentioning
confidence: 99%
“…This individual was found in a section of canal outside of the known range of P. clarkii and P. leniusculus and therefore may have been in an area unaffected by crayfish plague. Additionally, recent research has shown that A. leptodactylus may be able to develop a partial resistance to crayfish plague (Hokko et al, 2012). Of the 26 sites surveyed over 41 km; 15 were found to have P. clarkii present, indicating an approximate linear range of 11 km ( Figure 1).…”
Section: The North London Canal System and Its Crayfish Faunamentioning
confidence: 96%